A CASE REPORT OF A PATIENT WITH FOUR METACHRONOUS CANCERS - Janković, Kristina; Cvetanović, Ana (Acta medicae Medianae, 2024)
Multiple primary malignant neoplasms (MPMNs) are two or more histopathologically distinct malignancies in one or more organs such that one tumor is not a recurrence or metastasis of the other. Although there are well-known genes associated with hereditary cancers, sometimes it is not possible to find a genetic link between neoplasms. Our patient had four metachronous primary malignancies: breast cancer (BC), rectal cancer (RC), parotid cancer, lung cancer (LC), and highly suspected contralateral BC, over a 28-year period. We presented the challenges in diagnosis and therapeutic approach and highlighted the importance of genetic counseling and testing in these patients. To achieve better treatment, we need to find out which patients are at risk for MPMNs, and which tumors are more likely to occur synchronously or metachronously and enroll these patients in clinical trials.